Bone marrow cell response after injury and during early stage of regeneration is independent of the tissue‐of‐injury in 2 injury models. Issue 1 (25th July 2018) - Leitão, Luís; Alves, Cecília J.; Alencastre, Inês S.; Sousa, Daniela M.; Neto, Estrela; Conceiçâo, Francisco; Leitão, Catarina; Aguiar, Paulo; Almeida-Porada, Graça; Lamghari, Meriem
ABSTRACT: Selectively recruiting bone marrow (BM)‐derived stem and progenitor cells to injury sites is a promising therapeutic approach. The coordinated action of soluble factors is thought to trigger the mobilization of stem cells from the BM and recruit them to lesions to contribute to tissue regeneration. Nevertheless, the temporal response profile of the major cellular players and soluble factors involved in priming the BM and recruiting BM‐derived cells to promote regeneration is unknown. We show that injury alters the BM cellular composition, introducing population‐specific fluctuations during tissue regeneration. We demonstrate that injury causes an immediate, transient response of mesenchymal stromal cells and endothelial cells followed by a nonoverlapping increase in hematopoietic stem and progenitor cells. Moreover, BM reaction is identical whether the injury is inflicted on skin and muscle or also involves a bone defect, but these 2 injury paradigms trigger distinct systemic cytokine responses. Together, our results indicate that the BM response to injury in the early stages of regeneration is independent of the tissue‐of‐injury based on the 2 models used, but the injured tissue dictates the systemic cytokine response.—Leitão, L., Alves, C. J., Alencastre, I. S., Sousa, D. M., Neto, E., Conceição, F., Leitão, C., Aguiar, P., Almeida‐Porada, G., Lamghari, M. Bone marrow cell response after injury and during early stage of regeneration is independent of the tissue‐of‐injury in 2 injury models. FASEB J. 33, 857–872 (2019). www.fasebj.org